Alfabetização. Onde e como se forma o professor alfabetizador? - Lotfi, Maria do Carmo Ferreira (2011)
In this work, we made an analysis about how the formation of literacy teachers has been approached in the Pedagogy courses in São Paulo state. The low performance shown by the students of the Elementary School in the external evaluations points out the necessity of studies and effective actions to a better comprehension of this scenario. Considering the historical context, the educacional policy, its contributions and limitations, we tried to know the conceptions of literacy that there are in these institutions. The interviews with the teachers showed incoherence and difficulties in the formation of the literacy teacher, a social instrument that allows a better performance of the student in the reality in which he lives. The contribution of authors such as Gatti, Saviani, Sacristán, among others, the analysis of legal and institutional documents, besides the interviews with teachers of Educational courses, ruled the study of the above described theme